The role of the board in corporate purpose and strategy - Bood, Robert; Ees, Hans van, 1955-; Postma, Theo (Cambirdge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
This Element is an attempt to contribute to the extant literature on boards and corporate governance by exploring in detail the active involvement of the board in the purpose and strategy of the corporation in order to cope with a complex and uncertain environment.
Title from publisher's bibliographic system (viewed on 12 Sep 2022).
Keywords: Corporate governance; Branding (Marketing); Business planning; Boards of directors